A companion to Persius and Juvenal - Braund, Susanna Morton; Osgood, Josiah, 1974- (Chichester, West Sussex : Wiley-Blackwell, 2012)
A Companion to Persius and Juvenal breaks new ground in its in-depth focus on both authors as'satiric successors'; detailed individual contributions suggest original perspectives on their work, and provide an in-depth exploration of Persius'and Juvenal's afterlives. Provides detailed and up-to-date guidance on the texts and contexts of Persius and Juvenal Offers substantial discussion of the reception of both authors, reflecting some of the most innovative work being done in contemporary Classics Contains a thorough exploration of Persius'and Juvenal's afterlives.
PART I: Persius and Juvenal: Texts and Contexts -- PART II: Retrospectives: Persius and Juvenal as Successors -- PART III: Prospectives: The Successors of Persius and Juvenal
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Iuvenalis, Decimus Iunius, -- asi 67-asi 127; Persius, -- 34-62; 1.-2. století; básníci -- starověký Řím -- 1.-2. století; latinská starověká poezie -- 1.-2. století; satirická poezie -- starověký Řím -- 1.-2. století; literárněvědné rozbory; ancient Latin poetry -- 1st-2nd centuries; poets -- ancient Rome -- 1st-2nd centuries; satirical poetry -- ancient Rome -- 1st-2nd centuries; literary criticism and history; studie; sborníky; příručky; e-knihy online; studies; papers of several authors; handbooks and manuals; e-books online